Preservice Observation in Special Education: A Validation Study. (January 2021) - Pua, Daisy J.; Peyton, David J.; Brownell, Mary T.; Contesse, Valentina A.; Jones, Nathan D.
Advancing teacher candidates' overall competence through use of valid teacher observation systems should be an essential element of teacher preparation. Yet, the field of special education has not provided observation protocols designed specifically for preservice teachers that are founded in theoretical perspectives and research on effective instruction for students with learning and other high-incidence disabilities (SWDs). To address this need, a group of researchers in special education teacher preparation and measurement developed the Preservice Observation Instrument for Special Education (POISE). The POISE is an observation system rooted in effective special education practices that support the growth of preservice teachers who will serve SWD across instructional settings. The purpose of this article is to report on the development and psychometric properties of the POISE. Specifically, we employed Kane's argument-based validity approach to frame each stage in the development process of the POISE. We conducted two phases of content validation activities, development activities, and a pilot study to assess the degree to which scores from POISE provided evidence for the scoring, generalizability, and extrapolation inferences. In the end, the POISE represents a promising observation instrument for the development of special education teacher candidates.